THE EFFECT OF FIRM PERFORMANCE, LEVERAGE, FIRM SIZE, AND FIRM GROWTH ON AGENCY COST OF TRADING COMPANY IN INDONESIA, MALAYSIA, AND THAILAND: RESEARCH PERIOD OF 2009 – 2013 - Hamidah, Hamidah; Wicaksono, Ari; Ahmad, Gatot Nazir (Fakultas Ekonomi, Universitas Negeri Jakarta, 2017)
In this study,the author investigate the relationship of firm performance, leverage, firm size, and firm growth on the agency cost. In the company’s life, there are several holders an important role in the company itself. Agency theory explains that there are two parties to a company, the agent and principal.Researcher use firm performance, leverage, firm size, and firm growth as the independent variables. Researcher use the operational expenses ratio as proxy of agency cost. The high firm performance, expected to leads the lower agency cost.Researcher use the 19 listed trading firm on Indonesia, 26 listed trading firm on Malaysia, and 29 listed trading firm on Thailand. The empirical result show varying effect on agency cost in those three countries. The result of research depends on the characteristics of each country Keywords: Agency Cost, firm performace, leverage, firm size, firm growth